VIRTUAL PREDICTION OF THYMOQUINONE AND Î²-GLUCAN INTERACTION AS ESTROGEN RECEPTOR-ALPHA (ER-Î± RECEPTOR) MAY REDUCING ON THE BREAST CANCER SIGNALING PATHWAY - Rachmawati, Farida; Zaidah, Laili Nur; Mardhiyah, Rihadatul Aisy; Fatchiyah, Fatchiyah (JSMARTech: Journal of Smart Bioprospecting and Technology, 2019)
Many cases of chemical drug treatment in breast cancer patients result in a negative impact on drug resistance. Therefore the use of natural compounds such as ?-glucan on ajwa dates and thymoquinone on black cumin was expected to stop the process of cancer cell proliferation and to consume in long-term safety. This study aimed to predict the effect of thymoquinone and ?-glucan in reducing breast cancer cascade with molecular docking. This research was carried out in silico. The ligand and protein preparations were done using Discovery Studio 2016. We used Hex 8.0.0 for docking. Visualization was established using Discovery Studio 2016 as well. The results showed that thymoquinone and ?-glucan can undergo conformational changes in ligand binding domain (LBD) of ER-? receptor. The interaction between ER-? receptor with ?-estradiol (inhibited by thymoquinone-?-glucan) was suggested to be the best solution in downregulating breast cancer signaling pathway. This interaction showed more stable conformation with the smallest binding energy (-332,84 kcal/mol). The thymoquinone-?-glucan complex could block the His476 and Met438.